Assessment of Factors Associated with Healthcare Workers’ Knowledge, Attitude & Compliance with Standard Safety Rules - Ogbonda, Priscilia Nyekpunwo (British Journal of Healthcare and Medical Research, 2023)
The work environment is a sitting where there are possibilities of acquiring occupational illnesses, hence standard safety rules is very essential. Health workers (HWs) are victims of preventable and life-threatening work-related hazards due to their job description globally, most especially in Sub-Sahara Africa. Hence, this Study assessed barriers associated with health workers’ knowledge, attitude and compliance with standard safety rules in selected public hospitals in Rivers State, Nigeria. Descriptive cross-sectional design and a sample size of 347 were used. The study employed a multi-staged sampling technique and a structured instrument based on a coefficient of 0.88 as reliability. Descriptive statistics was used to analyze the data and results revealed there are existing standard safety rules in the hospital. Also, there is likelihood that management has initiated measures that enhances health worker’s knowledge and compliance with standard safety rules. Barriers to knowledge, attitude and compliance with standard safety rules are lack of periodic training/retraining, poor policy enforcement, unavailability of necessary documents on SSR, non- availability of PPEs, large number of patients, quick to provide service, staff are not punished for non-compliance and paying extra attention to SSRs guidelines is an unnecessary burden. Thus, there is need to improve health workers knowledge, attitude and compliance with standard safety rules in the aim to reduce exposure to infections and death. The study therefore recommends that hospital boards and health professional should enact enforceable integrated safety practice systems and incorporate occupational safety and health administration (OSHA) standard and best practice guidelines in the health sector.